2012
DOI: 10.17221/5478-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for haplotype-based association mapping in a complex pedigreed population

Abstract: AbStrAct:In association mapping, haplotype-based methods are generally regarded to provide higher power and increased precision than methods based on single markers. For haplotype-based association mapping most studies use a fixed haplotype effect in the model. However, an increase in haplotype length raises the number of parameters in the model, resulting in low accuracy of the estimates especially for the low-frequency haplotypes. Modeling of haplotype effects can be improved if they are assumed to be random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…We used a LMM that included random polygenic effects and random effects of the haplotype, i.e. random haplotype model (RHM) following [ 28 ]. The RHM model was: where q h 1 j and q h 2 j are random effects of the two haplotypes (one each from the sire and dam) carried by the j th individual, assumed to be normally distributed as , where σ h 2 is the variance of haplotype effects.…”
Section: Methodsmentioning
confidence: 99%
“…We used a LMM that included random polygenic effects and random effects of the haplotype, i.e. random haplotype model (RHM) following [ 28 ]. The RHM model was: where q h 1 j and q h 2 j are random effects of the two haplotypes (one each from the sire and dam) carried by the j th individual, assumed to be normally distributed as , where σ h 2 is the variance of haplotype effects.…”
Section: Methodsmentioning
confidence: 99%
“…Haplotypes were constructed for markers selected from LMM analyses using BEAGLE software [ 31 ]. We used a linear mixed effect model with random polygenic and haplotype effects following Boleckova et al [ 37 ] as follows: where, q h1j and q h2j are random effects of the two haplotypes carried by the j-th individual. Each haplotype effect is assumed independent and identically distributed (i.i.d), with a normal prior distribution , where is variance explained by the haplotype.…”
Section: Methodsmentioning
confidence: 99%
“…They reported that a higher accuracy of prediction was achieved for the validation dataset using models with random haplotype effects. Boleckova et al ( 2012 ) drew a similar conclusion after having tested linear models with haplotypes as explanatory variables. A like tendency was described by Mucha and Wierzbicki ( 2012 ), who used simulated data in a haplotype-based breeding value prediction study.…”
Section: Discussionmentioning
confidence: 82%
“…A similar approach was used by Huang et al ( 2007 ), who used the limiting value of this criterion computed as 1/ n and 2/ n , where n is the population size. Also, Kolbehdari et al ( 2007 ) and Boleckova et al ( 2012 ) showed that predictions of breeding values using haplotypes with higher frequencies were more accurate than using haplotypes with lower frequencies. In the study by Hayes et al ( 2006 ), haplotypes with a frequency of less than 1% were eliminated.…”
Section: Discussionmentioning
confidence: 99%